Interrelación e interdependencia en un territorio tradicional - Narváez-Collaguazo, Roberto Esteban (Pontificia Universidad Católica del Perú, 2024)
The Waorani, people of recent contact, and the family groups in isolation Tagaeiri Taromenane coexist in a particular territory, Yasuní, where the presence of external actors, and the extractive activities, generate conditions of pressure, activating conflicts. The most vulnerable peoples are those who they become victims, as happened in 2003, 2006 and 2013, with massacres that put the peoples in isolation the verge of disappearance. The article is an ethnographic research, for understanding the Waorani culture and of the family groups in isolation, identifying intergroup and intragroup relations, and the elements linked to conflict, which lead to establish the persistence of an ethos warrior and the persistence of a social order in relationships within the traditional territory of these societies.

El pueblo de reciente contacto waorani y los grupos familiares en aislamiento Tagaeiri Taromenane conviven en un territorio particular, en donde la presencia de actores externos, vinculados con las actividades extractivas, generan unas condiciones de presión, activando conflictos. Los pueblos más vulnerables son quienes se convierten en víctimas, tal como sucedió en 2003, 2006 y 2013, con masacres que ponen en el límite de la desaparición a los pueblos en aislamiento en el Yasuní. El artículo desarrolla, a partir de una investigación etnográfica, la comprensión de la particularidad cultural waorani y de los grupos familiares en aislamiento, identificando las relaciones intergrupales e intragrupales y los elementos vinculados con la conflictividad, que llevan a establecer la persistencia de un ethos guerrero y de un orden social en las relaciones dentro del territorio tradicional de estas sociedades.
Interrelation and Interdependence in a Traditional Territory
Keywords: Interrelation; Amazon; War; Ethos; Social order; Interrelación; Amazonía; Guerra; Orden social; Ethos; https://purl.org/pe-repo/ocde/ford#5.04.03